All in good time: Play development and tactics in foals (Equus caballus) - Maglieri, Veronica; Scopa, Chiara; Modica, Giuliana; Palagi, Elisabetta (Applied animal behaviour science, 2024)
Due to its ever-changing nature, play proves to be a promising subject for developmental investigations across mammal taxa, shedding light on the development of motor, social, and cognitive abilities. Compared to altricial mammals, horses (Equus caballus) show precocial locomotor and altricial socio/cognitive development, making them a valuable candidate for studying the potential roles of play from an early age. This research aims to map out the developmental trajectories of playful behaviours in semi-free ranging foals and test hypotheses on how they optimize their play sessions for greater success. Initial four weeks of foal life (period of dependence) are marked by locomotor play involving jumping, running, and circling, irrespective of the sex of the player, suggesting the significant role of kinematic activities in horse rapid motor maturation. Age does not seem to affect social play which is present along all the developmental periods of the foal life. Interestingly, foals with high-ranking mothers engaged more in social play, and unexpectedly, they self-restrained when playing with low-ranking mother foals. This self-restraint strategy enhances playful reciprocity, setting the stage for more rewarding and efficient play sessions. Mutual grooming is also employed by foals, contributing to the prolongation of these sessions. Consequently, the purpose of play in foals extends beyond merely enhancing dominance status, which is already inherited from their mothers, and encompasses elements beyond competitive dynamics. In summary, through play, foals assess and challenge their own as well as their peers' abilities, employing self-restraint and de-escalation techniques when necessary. Such playful behaviours, reminiscent of complex cognitive skills seen in humans and great apes, prompt us to explore similar capacities in other species, including farm animals. While the role of cognition in social play remains enigmatic, we need to expand our models if we want to open up new avenues for speculating about the evolution of play behaviour in mammals. •Weeks of life and social environment affect play development in foals.•High-ranking mare foals self-restraint when playing with lower-ranking playmates.•Mutual grooming increases the probability for social play to last longer.•Social play in foals extends beyond merely enhancing dominance status.